Evaluating the Management Information System of Integrated Medical Emergency Care in Batang Regency, Indonesia - Sulistiadi, Wahyu; Nurhidayah, Siti; Asyary, Al (International Journal of Online and Biomedical Engineering (iJOE), 2020)
An emergency can happen anywhere and anytime, especially in developing countries with a high potential for emergencies, such as Eastern European countries as well as Indonesia. This study aimed to find out the quality of PSC 119 Si Slamet as a prehospital emergency service innovation. The data collection in this study was carried out in a location, namely, Batang Regency, Indonesia, in May–June 2018. The qualitative data collection methods used in this study are in-depth interviews and document reviews. This study was using Service Quality (Servqual) questionnaire. The results show that PSC 119 Si Slamet provides easy access to emergency services to the community 24 hours a day and 7 days a week by simply calling 119 numbers, sending messages via SMS and WhatsApp, or using the Android-based application, with a maximum response time target of 10 minutes. Batang is one of the regencies (rural area) in Central Java province, located on the main coastline, with a hilly geographic condition with many derivatives, climbs, and sharp curves, which is one of the causes of the high number of traffic accidents in the area. This emergency care information systems, with Android-based application, was aimed at improving the quality of services in the health sector, especially emergency services. This service is of good quality as seen from the tangible, reliability, responsiveness, assurance, and empathy dimensions. However, in the implementation, the socialization aspect is not the best to some people. The recommendation given was the need to increase the PSC 119 socialization of Si Slamet not only regionally but also internationally to be massive, especially in developing countries.